2008
DOI: 10.1136/jme.2006.020032
|View full text |Cite
|
Sign up to set email alerts
|

Access to medical records for research purposes: varying perceptions across research ethics boards

Abstract: Large variation was found across sites in the requirement for consent for research involving access to medical records. REBs need training in best practices for protecting privacy and confidentiality in health research. A forum for REB chairs to confidentially share concerns and decisions about specific studies could also reduce variation in decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 15 publications
0
43
0
2
Order By: Relevance
“…The proper approach to protecting indirectly identifying information in any format, not just electronic, is debated by ethicists and review boards. 20 We limited the specificity of data to make it unable to be traced back to a unique individual, for instance by asking for the year of operation rather than a specific date. However, given that the line between anonymous and identifying information is not always distinct, we would recommend that any study of human subjects use technology that formally meets HIPAA standards.…”
Section: Lessons Learned and Future Possibilitiesmentioning
confidence: 99%
“…The proper approach to protecting indirectly identifying information in any format, not just electronic, is debated by ethicists and review boards. 20 We limited the specificity of data to make it unable to be traced back to a unique individual, for instance by asking for the year of operation rather than a specific date. However, given that the line between anonymous and identifying information is not always distinct, we would recommend that any study of human subjects use technology that formally meets HIPAA standards.…”
Section: Lessons Learned and Future Possibilitiesmentioning
confidence: 99%
“…Regulators and research ethics boards have been criticized for giving undue weight to the privacy of the individual (National Academy of Sciences 2006), and researchers continue to complain that privacy rules impede research (Cressey 2007;Ness 2007). Some have questioned whether individual informed consent is even necessary for participation in health services research (Cassell and Young 2002), while others struggle to interpret how privacy guidelines may affect the work of research ethics boards and researchers (National Academy of Sciences 2000; Willison et al 2008). Data custodians, various institutions that collect data and research ethics boards have struggled to determine what PHI can or should be shared among institutions and with researchers (Kulynych and Korn 2003;Willison et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some have questioned whether individual informed consent is even necessary for participation in health services research (Cassell and Young 2002), while others struggle to interpret how privacy guidelines may affect the work of research ethics boards and researchers (National Academy of Sciences 2000; Willison et al 2008). Data custodians, various institutions that collect data and research ethics boards have struggled to determine what PHI can or should be shared among institutions and with researchers (Kulynych and Korn 2003;Willison et al 2008). The results of the present study indicate that this uncertainty extends to the level of members of various professional groups as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willison et al 23 evaluated the diversity of conducts by the REC when approving protocols of which source of data consisted of medical files. They interviewed REC coordinators related to Schools of Medicine in Canada and reported that 47.0% of them require individual consent from the research subject.…”
Section: Discussionmentioning
confidence: 99%